SPORTS PARTICIPATION ASSOCIATED WITH HEALTH RISK BEHAVIORS IN ADOLESCENT ATHLETES - Campos,Jhonatan Gritten (2020)
ABSTRACT Introduction Participation in structured sports activities is essential for the health of adolescents, since adolescence is a period in which several physical, psychological, cognitive and social changes occur, where the sense of autonomy in decision-making may prompt them to adhere to certain health risk behaviors. Objective To verify the association of sports participation with health risk behaviors in adolescent athletes. Methods A cross-sectional study with 367 athletes (15.68 ± 0.78 years) from Curitiba/PR (state of Paraná). Associated factors and health risk behaviors (HRB) were assessed using questionnaires. Poisson regression with robust variance was used to analyze factors associated with HRB, adopting p <0.05. Results Team sport was positively associated with longer TV viewing time (PR: 3.11; 95% CI: 1.13-8.58). Years of participation were positively associated with longer TV viewing (PR: 1.14, 95% CI: 1.01-1.29) and video game playing time (PR: 1.12, 95% CI: 1.01-1.25). Negative associations were found for weekly training volume in longer video game playing time (OR: 0.92, 95% CI: 0.86-0.99), low vegetable consumption (PR: 0.98, 95% CI: 0.96-0.99), and in light (PR: 0.95, 95%CI: 0.92-0.99) and excessive (PR: 0.94, 95%CI: 0.89-0.99) alcoholic consumption. Conclusion The weekly training volume favors a reduction in video game playing time, lower alcohol consumption, and increased vegetable consumption in adolescent athletes. Level of Evidence III; Diagnostic studies - Investigation of a diagnostic test; Study of non-consecutive patients, without a “gold standard” applied uniformly.